120k views
4 votes
Find (g*f)(3)
f(x)= 3x-2
g(x)=x2

Find (g*f)(3) f(x)= 3x-2 g(x)=x2-example-1
User Femaref
by
5.4k points

2 Answers

2 votes

Answer:

49 choice C is the correct solution

Explanation:

The composite function, (g o f) simply means we substitute the function f(x) in place of x in the function g(x). since g(x) =x^2, (g o f) =(f(x))^2 = (3x-2)^2. The final step is to substitute x=3 in this expression which yields 49

User Justinpawela
by
5.5k points
1 vote

Answer:

C

Explanation:

( g o f)(­ 3) means to substitute the value x=3 after substituting f(x) into g(x).


(3x-2)^2\\(3(3)-2)^2\\(9-2)^2\\7^2\\49

User Aart Stuurman
by
5.5k points